The emergence of China, Inc.: behind and beyond the trade war. Issue 4 (13th May 2020) - Li, Shaomin; Farrell, Matthew
Abstract : Purpose: Answering the call to study important issues in the real world (Buckley et al., 2017; Delios, 2017; Phan, 2019), and motivated by the trade war between the US and China, the authors look beyond it to examine the more fundamental issues behind it. From a political economy perspective, the authors examine the interplay of government, society and firms in China to identify new phenomena that may impact business with, and research on, China. Design/methodology/approach: A multi-case qualitative method is used to present and analyze evidence and develop our arguments. Specifically, we use scholarly sources, anecdotal evidence, reports, statistics and government documents and policies to support our arguments. Findings: After four decades of economic reform, the Chinese Communist Party (CCP) controls every aspect of the society. Living, working and doing business are not a right but a privilege granted by the party. To a great degree, state-owned firms are business units/subsidiaries, and private/foreign firms are franchisees of the party, with the party leader being the CEO of China, Inc. The interplay between China and other countries is essentially a competition between a huge corporation and other states. Practical implications: At the firm level, our study suggests that for MNCs dealing with Chinese firms, they need to know that Chinese firms are units of China, Inc. Practitioners should take into account the long-term strategic goals of the CCP as well as business considerations when dealing with Chinese partners or competitors. Social implications: At the country level, our study shows that other countries dealing with China must be aware that they are dealing with a huge corporation. Originality/value: That the CCP runs China as a corporation is a new perspective that will help the international community reexamine global competition.